The Influence of Leadership Style, Compensation, and Organizational Culture on Job Satisfaction at SMK Muhammadiyah 2 Pekanbaru - Jabarullah Jabarullah (Journal of Educational Sciences, 2026)
Integrated empirical investigation of the organizational factors shaping teacher job satisfaction within Islamic value-based private vocational schools remains scarce in the existing literature. This study examined the simultaneous influence of leadership style, compensation, and organizational culture on teacher job satisfaction at SMK Muhammadiyah 2 Pekanbaru, a Muhammadiyah-based vocational institution recognized as a Center of Excellence, offering a novel perspective on how Islamic institutional values mediate the relationship among these three determinants. A quantitative survey design was adopted, engaging all 74 employees as respondents through census sampling. Instruments were validated using Pearson correlation and Cronbach Alpha reliability testing. Data were analyzed through multiple regression with partial t-tests, while the F-test confirmed the simultaneous significance of the model and R² indicated the collective explanatory power of the independent variables. Results revealed that leadership style (t = 2.869, sig. = 0.005), compensation (t = 2.026, sig. = 0.047), and organizational culture (t = 2.886, sig. = 0.005) each exerted a positive and significant influence on teacher job satisfaction. The Muhammadiyah school context, grounded in Akhlakul Karimah and da'wah-oriented professional ethics, provides a distinctive framework through which leadership, compensation, and culture collectively cultivate educator satisfaction beyond conventional organizational settings.